Underdevelopment and agrarian structure in Pakistan - Khan, Mahmood Hasan (Boulder, Colo. : Westview Press, 1981)
In this analysis of the relationship between agrarian structure and agricultural development in Pakistan, the author investigates the slow and uneven performance of agriculture and explores probable causes.
Includes index.
includes Bibliographical references : p. 293-300
uaa 25/01/2019
Loan
Keywords: Land reform; Land tenure; Agriculture